Development of a Web-Based Online Judge for Java Programming Examinations to Enhance Interactive Learning Environments - Putra, Muhammad Trio Maulana; Sa’adah, Nurul Laili; Kurnia, Nicky Dwi; Ani, Febi Warta Nur (Universitas Trunojoyo Madura, 2025)
This paper addresses the challenges in traditional programming assessment, such as scalability and delayed feedback. We present the development of a web-based examination platform for the Java programming language. The system is designed with a decoupled architecture, integrating the CodeMirror editor to create an interactive learning environment and leveraging the Glot.io API for secure, sandboxed code execution. This approach mitigates security risks associated with evaluating untrusted code and provides students with real-time, automated feedback. The resulting platform offers a robust, secure, and pedagogically enhanced solution for online programming assessment, improving both the efficiency for instructors and the learning experience for students.